Teachers’ learning in lesson study: insights provided by a modifed version of the interconnected model of teacher professional growth - Ponte, João Pedro da (2022)
In the research reported in this paper, using a modifed version of the interconnected model of teacher professional growth (IMTPG) proposed by Clarke and Hollingsworth (Teaching Teacher Educ 18:947–967, 2002), we aimed to understand the learning dynamics in a lesson study of a group of fve teachers of grades 5–6, during their work around mathematical tasks and in the elaboration and analysis of a diagnostic test of students’ knowledge. We draw on examples from a lesson study that took place in a school in Lisbon, involving fve teachers that constituted the whole mathematics group of the school. The main feature of our adaptation is the consideration of a Group Domain instead of the Personal Domain of the original model. In the original model, the Domain of Practice had a broad defnition but usually it was restricted to classroom experimentation. In the research reported in this paper, the lesson study sessions were taken as part of the Domain of Practice. For data collection, there was audio and video recording of the lesson study sessions and of the research lesson and the writing of a research journal. Data analysis was done using the modifed IMTPG. The results suggest that this model is helpful in understanding the processes that make lesson study a valuable professional development setting, contributing to responding to the question of ‘how lesson study works’ (Lewis et al., Theory and practices of lesson study in mathematics: an international perspective, Springer, New York, 2019). In addition, the use of this model showed that the lesson study promoted the teachers’ development regarding knowledge of didactics, especially knowledge of students and their learning processes and of teaching practice.